THE EFFECT OF A COMBINATION OF VEGETABLE PESTICIDES ON THRIPS PEST ATTACKS ON VEGETATIVE GROWTH OF GREEN BEANS (Vigna radiata L.) - Lubis, Wisuda Pramarta; Idris, M.; Rahmadina, Rahmadina (Program Studi Pendidikan Biologi, 2024)
The productivity of green beans according to BPS North Sumatra data for 2021 from 2019 to 2021 has decreased, with an average of 2.52%. One of the causes of decreased green bean productivity is the occurrence of thrips pest attacks. One alternative that can be done to overcome thrips pests is to use plant-based pesticides. This study aims to determine the effect of applying a combination of lemongrass and kenikir vegetable pesticides on thrips on the vegetative growth of green bean plants and to determine the most effective concentration of the use of vegetable pesticides. This study used a non-factorial Randomized Block Design (RBD), namely concentrations (P0 = control; P1 = 100 ml of lemongrass and marigold extracts/L water; P2 = 200 ml of lemongrass and marigold extracts/L of water; P3 = 300 ml of lemongrass and marigold extracts and kenikir/L of water). The results showed that P3 (300 ml/L) treatment had a very significant effect on attack intensity of 14.91%, attack percentage of 25.35% and leaf area index of 0.46cm. Meanwhile, each treatment P0, P1, P2, P3 had no significant effect on plant height and leaf chlorophyll levels.